2012
DOI: 10.1111/j.1537-2995.2012.03591.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient blood transfusion management: discharge hemoglobin level as a surrogate marker for red blood cell utilization appropriateness

Abstract: In aggregate, overutilization exceeded 20%. At the focus hospital, approximately one-quarter of patients receiving transfusions had a Hb concentration greater than 10.0 g/dL at discharge. Transfused patients' discharge Hb concentration represents an effective indicator for retrospective monitoring of transfusion appropriateness. In light of the large number of patients receiving even number transfusions, reviewing Hb levels after transfusion of each RBC unit could reduce unnecessary transfusions. Retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…If and how many red blood cell concentrates are transfused (in default of approved artificial oxygen carriers) not only depends on the individual patient’s condition but also on the hospital’s practice, whereas at a hemoglobin decrease below 6 g/dl transfusion of red blood cell concentrates is generally indicated [20]. If transfusion is inalienable, until now, usually 2 or more red blood cell concentrates are required, as the average increase in hemoglobin level per unit red blood cell concentrate is only 1.0 g/dl [21]. Therefore, the tolerance of high quantities of foreign particles in the intravascular system is a prerequisite for the successful use of microcapsules as artificial oxygen carriers and implies both, the occurrence and the monitoring of new toxicity profiles.…”
Section: Discussionmentioning
confidence: 99%
“…If and how many red blood cell concentrates are transfused (in default of approved artificial oxygen carriers) not only depends on the individual patient’s condition but also on the hospital’s practice, whereas at a hemoglobin decrease below 6 g/dl transfusion of red blood cell concentrates is generally indicated [20]. If transfusion is inalienable, until now, usually 2 or more red blood cell concentrates are required, as the average increase in hemoglobin level per unit red blood cell concentrate is only 1.0 g/dl [21]. Therefore, the tolerance of high quantities of foreign particles in the intravascular system is a prerequisite for the successful use of microcapsules as artificial oxygen carriers and implies both, the occurrence and the monitoring of new toxicity profiles.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of change in RBC use probably reflects the lack of prospective review. Although use of RBCs generally met the criteria for transfusion on retrospective review, as previously reported, 36 there is evidence that patients are often given excessive amounts of transfused products once transfusion is initiated. 36 The increase in cryoprecipitate use that we observed may be a random event.…”
Section: Discussionmentioning
confidence: 83%
“…Although use of RBCs generally met the criteria for transfusion on retrospective review, as previously reported, 36 there is evidence that patients are often given excessive amounts of transfused products once transfusion is initiated. 36 The increase in cryoprecipitate use that we observed may be a random event. However, because we encouraged the use of cryoprecipitate in lieu of FFP in some circumstances, this increase may have resulted from positive intervention and may have been partly responsible for the reduction in FFP use.…”
Section: Discussionmentioning
confidence: 83%
“…Typically, the discharge hemoglobin after surgery for spinal deformity has been reported to be approximately 10 g/dL. 85,86 Edwards et al 87 conducted a retrospective chart review of 475 patients at a single institution on multiple specialty services. They found that discharge hemoglobin was a significant indicator of overutilization of blood transfusion and that a large portion of patients who had discharge hemoglobin of 10.0 g/dL or more could have avoided at least 1 unit of blood transfusion.…”
Section: Indications To Transfusementioning
confidence: 99%